Genetic variants associated with platelet count are predictive of human disease and physiological markers - Evgenia Mikaelsdottir (Nature Portfolio, 2021)
Evgenia Mikaelsdottir et al. report a study of variants associated with platelet count among European individuals where they identify 577 associations. They also report a genetic overlap between platelet count and human diseases, including myeloproliferative neoplasms, rheumatoid arthritis, and hypertension, as well as a genetic overlap between platelet count and various physiological markers.